2013
DOI: 10.1007/s12282-013-0460-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual assessment of Ki67 at a glance is an easy method to exclude many luminal-type breast cancers from counting 1000 cells

Abstract: Eye-10 is far easier than counting many cancer cells and useful for classifying breast cancers. Eye-10 can exclude obviously high and low Ki67 cases, leaving a "gray zone" around a cutoff point. Combining Eye-10 and manual counting is a good candidate for a standard method to evaluate Ki67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…in the range of Ki67 LI 10-30 % [3]. A visual scoring methodology proposed by Hida et al, might be used as method of choice for “low” (Ki67 LI <10 %) or “high” (Ki67 LI >30 %) proliferatively active cases, leaving behind “grey zone” cases, which requires more precise methodologies [34]. …”
Section: Discussionmentioning
confidence: 99%
“…in the range of Ki67 LI 10-30 % [3]. A visual scoring methodology proposed by Hida et al, might be used as method of choice for “low” (Ki67 LI <10 %) or “high” (Ki67 LI >30 %) proliferatively active cases, leaving behind “grey zone” cases, which requires more precise methodologies [34]. …”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that visual assessment of Ki67 at a glance with a 10-grade scale (Eye-10) is easy and can help classify luminal-type breast cancers 5. Here, we have modified it into a simpler 5-grade scale, Eye-5.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation and IHC staining on representative blocks of each tumour was performed as previously described 5. Ki67 antibody (MIB-1, 1:100) was from DAKO (Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Akira I. Hida et al showed a significant positive correlation between Eye-10 and Ki67LI with the magnitude of (r=0.94). They showed that the visual assessment of Ki67 at a glance with a 10-grade scale (Eye-10) is an easy method (a rational alternative for Ki67LI) and can exclude obviously high and low Ki67 breast tumors, leaving a gray zone around a cut-off point (5).…”
Section: Discussionmentioning
confidence: 99%